Molybdenum oxide sintered body, sputtering target material, and oxide thin film

By adding specific metal dopants and alkaline earth metal oxides to the molybdenum oxide and performing pressure-free sintering, the sinterability and density problems of difficult-to-sintering molybdenum oxide are solved, and oxidation with high density, low resistance and low reflection characteristics is formed. The sintered body and sputtering target material improve the chemical resistance and heat resistance of the film, and solve the problems of film quality and stability in the prior art.

CN119137085APending Publication Date: 2024-12-13LT METAL CO LTD

Patent Information

Application Number
CN202380014461.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-13
Filing Date
2023-11-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to improve the sinterability and density of difficult-to-sinter molybdenum oxides, resulting in insufficient chemical resistance and heat resistance of films during long-term use, and foreign matters are easily generated during sputtering, which reduces the film quality.

Method used

By adding specific metal dopants to the molybdenum oxide, such as molybdenum, titanium, chromium, tungsten and copper, combined with alkaline earth metal oxides, and performing pressure-free sintering, optimizing the grain size and composition of the sintered body, forming high density, Oxide sintered bodies and sputtering targets with low resistance and low reflection characteristics.

Benefits of technology

It realizes the improvement of the sintering property and density of the molybdenum oxide sintered body under pressure-free conditions, ensures high quality of the film and long-term use stability, reduces resistance and reflectivity, and expands the material of liquid crystal displays and organic light-emitting diode thin film transistors. Scope of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137085A_ABST
    Figure CN119137085A_ABST
Patent Text Reader

Abstract

The invention provides a molybdenum-based oxide sintered body, a sputtering target material containing the sintered body, and an oxide thin film formed by the sputtering target material. In the present invention, a specific dopant is added to a molybdenum oxide and a niobium oxide that are difficult to sinter in a prescribed content range, and it is possible to simultaneously ensure improved sinterability, high density characteristics, and uniformity, low reflection, and low resistance characteristics of a thin film obtained by controlling particle growth even if pressureless sintering is performed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an oxide sintered body used in a thin film transistor (TFT) structure of a liquid crystal display (LCD) and / or an organic light emitting diode (OLED), a sputtering target containing the above-mentioned sintered body, and a thin film preparation using the same. More specifically, it relates to an oxide sintered body and a sputtering target that improve density characteristics and control grain size refinement by adding some elements, and an oxide thin film having low resistance and low reflection characteristics using the same. Background Art

[0002] Generally, a conductive film with low reflectivity is used in a flat panel display (FPD), a touch screen panel, a solar cell, a light emitting diode (LED), and an organic light emitting diode (OLED).

[0003] Among the materials concerned, indium oxide-tin oxide (In2O3-SnO2) (indium tin oxide (ITO)) is a representative example, and an indium tin oxide composition is used to form a conductive film with high visible light transmittance and electrical conductivity. Although such an indium tin oxide composition has excellent low reflectivity performance, its economic efficiency is low, and therefore, research has been conducted on materials that completely or partially replace indium oxide.

[0004] However, these studies have focused only on the low reflectivity of thin films formed using target materials, and therefore, it is necessary to consider properties such as chemical resistance and heat resistance that can improve the reliability of thin films during long-term use.

[0005] On the other hand, molybdenum oxide itself is a difficult-to-sinter material. When such a difficult-to-sinter and low-density molybdenum oxide ceramic material is used, it is not only difficult to form a high-density (for example, a relative density of more than 90%) target, but also foreign matter will be generated due to back deposition and agglomeration when the prepared target is sputtered, resulting in a decrease in the physical properties of the film.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Korean Patent Publication No. 10-2020-0069314 Summary of the invention

[0009] Technical issues

[0010] The present invention is proposed to solve the above-mentioned problems. The purpose of the present invention is to provide a new molybdenum oxide sintered body which can improve the sinterability, control the grain size and ensure high density even when sintered in a pressureless state by adding a specific metal dopant within a specified content range to a difficult-to-sinter molybdenum oxide as a main raw material, a sputtering target containing the above-mentioned sintered body, and an oxide film formed therefrom with improved low reflection and low resistance characteristics.

[0011] Other objects and advantages of the present invention will be more clearly described through the following detailed description of the invention and the scope of protection of the invention.

[0012] Technical Solution

[0013] In order to achieve the technical problem, the present invention provides an oxide sintered body, comprising molybdenum oxide (M1); niobium oxide (M2); at least one alkaline earth metal oxide (M3); and one or more metals (M4) selected from the group consisting of molybdenum (Mo), titanium (Ti), chromium (Cr), tungsten (W) and copper (Cu). The metal (M4) is contained in an amount of 3 weight percent to 60 weight percent relative to the total weight of the sintered body.

[0014] In one embodiment of the present invention, the sintered body may contain 5 weight percent to 55 weight percent of the metal (M4) relative to the total weight of the sintered body.

[0015] In one embodiment of the present invention, the average grain size (D50) of the oxide sintered body grains may be 80% or less compared to the average grain size (D50) of the oxide sintered body not containing the metal (M4).

[0016] In one embodiment of the present invention, the sheet resistance of the oxide sintered body may be 60% or less compared to the sheet resistance of an oxide sintered body not containing the metal (M4).

[0017] In one embodiment of the present invention, the oxide sintered body may include Mo (1-x) Nb x O2 (x is 0 to 0.25) crystal phase and metal (M4) crystal phase.

[0018] In one embodiment of the present invention, the oxide sintered body can be formed by mixing molybdenum oxide (M1), niobium oxide (M2), at least one alkaline earth metal oxide (M3) and metal (M4) to prepare a molded body and then pressurelessly sintering the mixture under atmospheric pressure.

[0019] In one embodiment of the present invention, the molybdenum oxide (M1) may include at least one of MoO2 and MoO3, and may include 20 weight percent to 70 weight percent of the molybdenum oxide (M1) relative to the total weight of the oxide sintered body.

[0020] In one embodiment of the present invention, based on 100 weight percent of the oxide sintered body, the molybdenum oxide and the niobium oxide are contained in an amount greater than or equal to 45.0 weight percent and less than 95 weight percent, and the content ratio of the molybdenum oxide to the niobium oxide may be 80:20 to 45:55 by weight.

[0021] In one embodiment of the present invention, the alkaline earth metal oxide (M3) may include at least one selected from the group consisting of CaCO3 and MgO.

[0022] In one embodiment of the present invention, based on 100 weight percent of the oxide sintered body, the alkaline earth metal oxide (M3) may be included in an amount greater than 0 weight percent and less than or equal to 10 weight percent.

[0023] In one embodiment of the present invention, the weight ratio of the at least one alkaline earth metal oxide (M3) to the metal (M4) may be 1:1-20.

[0024] In one embodiment of the present invention, the average grain size (D50) of the grains constituting the pressureless sintered oxide sintered body may be 5 μm to 30 μm, and the specific resistance may be 3×10 -3 Ωcm or less, and the relative density can be above 80%.

[0025] Furthermore, the present invention provides a sputtering target including the above-mentioned oxide sintered body.

[0026] At the same time, the present invention provides an oxide thin film formed by the above-mentioned sputtering target.

[0027] In one embodiment of the present invention, the reflectivity of the oxide film for light with a wavelength of 550 nm may be less than 25%, and the thickness may be to When the sheet resistance can be 2.6×10 4 Ω / sq or less.

[0028] Effects of the Invention

[0029] According to one embodiment of the present invention, a metal dopant that inhibits the growth of grains constituting the sintered body is added to the difficult-to-sinter molybdenum oxide within a specified content range, thereby improving the sintering properties of the molybdenum oxide sintered body even in the absence of pressure, thereby ensuring optimization of particle size, low resistance, low reflection and high density.

[0030] Therefore, the molybdenum oxide-based sintered body and sputtering target of the present invention can be effectively used to form electrodes or wirings used in thin film transistor structures of liquid crystal displays and organic light emitting diodes.

[0031] The effects of the present invention are not limited to the above-exemplified contents, and include more various effects in this specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The photographs show the microstructure and average grain size of the oxide sintered bodies prepared in Examples 1 to 5 in which molybdenum metal (M4) was added.

[0033] Figure 2 The photographs show the microstructure and average grain size of the oxide sintered bodies prepared in Comparative Examples 1 and 2 without adding molybdenum metal (M4).

[0034] Figure 3 Graph showing the average grain size of the pressureless sintered oxide sintered bodies in Examples 1 to 5 and Comparative Examples 1 and 2.

[0035] Figure 4 Graph showing the change in relative density of the oxide sintered bodies prepared in Examples 1 to 5 and Comparative Examples 1 and 2 as a function of sintering temperature.

[0036] Figure 5 Graph showing the change in shrinkage of the oxide sintered bodies prepared in Examples 1 to 5 and Comparative Examples 1 to 2 as a function of sintering temperature.

[0037] Figure 6 Graph showing the change in sheet resistance per unit film of thin films formed from the oxide sputtering targets of Examples 1 to 5 and Comparative Example 2 as a function of thickness.

[0038] Figure 7 Graphs showing average reflectivity per unit film and sheet resistance of thin films formed from the oxide sputtering targets of Examples 3 to 5.

[0039] Figure 8 Graph showing the change in average reflectivity per unit film of thin films formed from oxide sputtering targets of Examples 1 to 5 and Comparative Example 2 as a function of thickness.

[0040] Fig. 9 1 is an X-ray diffraction (XRD) graph of the oxide sintered bodies prepared in Example 1, Example 4, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0041] All terms (including technical and scientific terms) used in this specification can be used with the meanings commonly understood by ordinary technicians in the technical field to which the present invention belongs. In addition, unless otherwise clearly defined, the terms defined in commonly used dictionaries are not interpreted in an ideal or exaggerated manner.

[0042] Throughout this specification, when it is mentioned that a part "includes" a certain structural element, unless there is a special record to the contrary, it means that other structural elements may also be included, rather than excluding other structural elements. In addition, throughout this specification, being "on" or "above" not only refers to being above or below the object part, but also means including the situation where there are other parts between them, and does not necessarily mean being located on the upper side based on the direction of gravity. Moreover, the terms "first" and "second" in this application do not indicate any order or importance, but are used to distinguish between the various structural elements.

[0043] Generally, MoO2-Nb2O5 materials used in existing n-type semiconductor thin films are prepared by pressure sintering. However, in the case of pressure sintering, the cost of the preparation process of pressurizing the equipment increases, which is not suitable for mass production. In addition, the preparation process of applying high pressure has limitations in terms of the size of the sintered body.

[0044] In order to solve the above problems, the pressureless sintering of MoO2-Nb2O5 materials is difficult to apply due to the limitation of the increase of sintering density. In addition, when the sintering temperature is increased, the density decreases due to the increase of melting and volatilization. That is, heat is required as a driving force during sintering. Generally, the higher the heat, the more conducive it is to ensure sinterability (density). However, on the contrary, some elemental materials reduce density due to volatilization and other problems.

[0045] On the other hand, the inventors confirmed in Korean Patent Application No. 10-2022-0132119 that a small amount of alkaline earth metal oxide dopant (M3) that assists sintering in a difficult-to-sinter material composed basically of molybdenum oxide and niobium oxide can simultaneously ensure the effects of improving sintering properties and ensuring high density even during pressureless sintering under atmospheric pressure. In this case, the bonding between particles in the oxide sintered body can be ensured by adding an alkaline earth metal oxide (M3) dopant, for example, by adding CaCO3, MgO, etc., but this causes the phenomenon of increasing the size of particles in the sintered body. When the grain size of the sintered body increases as described above, the particles unevenly form a film during the sputtering process to produce foreign matter, which ultimately leads to reduced quality and reliability of the oxide film.

[0046] Therefore, in the present invention, an alkaline earth metal oxide dopant (M3) that assists sintering and a specific metal (M4) that improves the homogeneity of the thin film by suppressing the grain growth of the sintered body and optimizing the particle size are mixed in a difficult-to-sinter material composed basically of molybdenum oxide (M1) and niobium oxide (M2), and the ratio (composition) of these metal elements is adjusted. Therefore, in the present invention, not only a high-density target material is obtained by improving the sintering property, but also the composition unevenness and the formation of foreign matter such as back deposition and agglomeration that may occur during sputtering are improved by controlling the particle growth, so that a high-quality thin film can be obtained. In addition, by using a high content of metal (M4) dopant to simultaneously ensure the low resistance and low reflection characteristics of the oxide thin film formed by the sintered body, the material application range of the thin film transistor set in the existing liquid crystal display and organic light-emitting diode can be expanded.

[0047] Oxide sintered body and high density target for sputtering

[0048] One example of the present invention is a molybdenum-based oxide sintered body used in a thin film transistor structure of a liquid crystal display and / or an organic light emitting diode, and a high-density sputtering target containing the same.

[0049] Generally, in the case of sintering oxide sintered bodies, heat or pressure is required as a driving force. In this case, the higher the heat and pressure, the more the sinterability of the sintered body is ensured, and the more conducive to densification. On the contrary, some materials have problems such as melting and volatilization, which reduces the density. In the present invention, molybdenum oxide and niobium oxide are used as the basic composition, by synthesizing the intermediate phase of the main raw materials (for example, a solid solution between molybdenum oxide and niobium oxide) and adding additional elements (for example, M3, M4 dopants), even if pressureless sintering can ensure the density (densification) of the sintered body that can be used as a sputtering target, and by optimizing the particle size, the uniformity, low resistance, and low reflection characteristics of the thin film formed by sputtering are ensured.

[0050] In one example, the oxide sintered body comprises: molybdenum oxide (M1); niobium oxide (M2); at least one alkaline earth metal oxide (M3); and one or more metals (M4) selected from the group consisting of molybdenum, titanium, chromium, tungsten and copper. The metals (M4) are contained in a specified content (e.g., 3-60 weight percent).

[0051] Hereinafter, each component will be described in detail.

[0052] The molybdenum oxide contained in the oxide sintered body of the present invention is a main component constituting the sintered body.

[0053] Molybdenum oxide (M1) is a component such as MoO2, MoO3, MoO4, etc., which has a form in which molybdenum and oxygen are combined. In the present invention, MoO2, MoO3, or a mixture of MoO2 and MoO3 can be used as the molybdenum oxide (M1). In this case, when a mixture of MoO2 and MoO3 is used as the molybdenum oxide, the mixing ratio between them is not particularly limited and can be appropriately adjusted within the usual range known in the technical field to which the present invention belongs. On the other hand, the melting point of MoO3 is about 800°C, and it volatilizes at a high temperature of more than 1000°C. Therefore, preferably, MoO2 is used as the molybdenum oxide (M1) in the present invention in which pressureless sintering is performed at a high temperature of more than 1000°C.

[0054] Furthermore, one of the additive components contained in the oxide sintered body of the present invention is niobium oxide (M2).

[0055] The niobium oxide (M2) is an oxide dopant for improving chemical resistance and heat resistance, and the chemical resistance and heat resistance of molybdenum oxide can be improved by adding the metal oxide. The niobium oxide is not particularly limited as long as it is a component in which niobium and oxygen are combined, and may be, for example, Nb2O5. In the following description, the niobium oxide component is marked as M2.

[0056] Another additional component contained in the oxide sintered body of the present invention is a metal oxide (M3) containing at least one alkaline earth metal.

[0057] In one example, the metal oxide (M3) may include at least one of barium (Ba), calcium (Ca), magnesium (Mg) and strontium (Sr), and specifically, may include a metal oxide (M3) containing at least one of calcium and magnesium.

[0058] The metal oxide (M3) containing an alkaline earth metal plays a role as a dopant that assists the sintering of the difficult-to-sinter molybdenum oxide to show the effect of increasing the density. The chemical resistance and heat resistance of the molybdenum oxide can be improved by adding the above-mentioned metal oxide (M3). The above-mentioned metal oxide (M3) containing an alkaline earth metal is not particularly limited as long as it is a component having a form in which at least one element (A) of calcium and magnesium is combined with oxygen. For example, it can contain one or more selected from the group consisting of CaCO3 and MgO.

[0059] One of the additive components contained in the oxide sintered body of the present invention is one or more metals (M4) selected from the group consisting of molybdenum, titanium, chromium, tungsten and copper.

[0060] In the past, when the density of the oxide sintered body was low (relative density ≤ 90%), foreign matter was generated in the thin film due to back deposition and agglomeration during sputtering. Therefore, the higher the density, the more advantageous it is in the sputtering process. On the other hand, different particles on the surface of the target material are pulled off during sputtering. In this case, the pull-out position is vacant, and the smaller the particle, the smaller the pull-out position, thereby reducing the curvature of the sputtered target surface. Therefore, at the same density, the smaller the size of the particles constituting the oxide sintered body, the more uniformly the particles can form a film during the sputtering process, thereby ensuring the effect of improving the composition unevenness and foreign matter generation that may occur in the sputtering process.

[0061] The metal (M4) used in the present invention plays a role in improving the compositional non-uniformity and foreign matter generation that may occur in the sputtering process by regulating the growth of particles constituting the oxide sintered body. That is, the metal (M4) inhibits the particle growth caused by the addition of metal oxides (M3) such as CaCO3 and MgO and seeks to homogenize and refine the grain size of the sintered body, thereby improving the quality of the oxide film formed by sputtering. In addition, the low resistance characteristics can be ensured by reducing the sheet resistance of the unit film due to the conductivity of the metal. Moreover, as a metal dopant that exhibits a density increase effect by assisting the sintering of molybdenum oxide, the high density, chemical resistance and heat resistance of molybdenum oxide can be improved by adding the above-mentioned metal. In the following description, one or more components selected from molybdenum, titanium, chromium, tungsten and copper are marked as M4, preferably molybdenum.

[0062] The metal oxide sintered body comprising molybdenum oxide (M1), niobium oxide (M2), at least one metal oxide containing alkaline earth metal (M3), and metal (M4) may contain 45.0 weight percent or more and less than 95 weight percent of molybdenum oxide (M1) and niobium oxide (M2), 0 weight percent or more and less than 10 weight percent of alkaline earth metal oxide (M3), and 3.0 weight percent to 60 weight percent of metal (M4), based on 100 weight percent of the sintered body. More specifically, the composition may be: 45.0 weight percent to 90.0 weight percent of molybdenum oxide (M1) and niobium oxide (M2); 0.5 weight percent to 5.0 weight percent of alkaline earth metal oxide (M3); and 5.0 weight percent to 55 weight percent of metal (M4).

[0063] The content ratio of molybdenum oxide (M1) to niobium oxide (M2) is 80:20 to 45:55 by weight, specifically, 72:28 to 47:53 by weight, and more specifically, 63:37 to 56:44 by weight. In the present invention, when the molybdenum oxide, for example, MoO2, accounts for 20 to 70 weight percent, specifically, 20 to 68 weight percent, relative to the total relevant metal oxide sintered body, it can have low reflection characteristics when evaporated into a thin film.

[0064] Furthermore, the oxide sintered body may contain at least one alkaline earth metal oxide (M3) and a metal (M4) constituting the oxide sintered body in a weight ratio of 1:1 to 20, and specifically, in a weight ratio of 1:10 to 15.

[0065] The oxide sintered body of the present invention can contain oxides of various metal components (M1, M2, M3, M4) according to the target composition. For example, after mixing molybdenum oxide (M1), niobium oxide (M2), metal oxide containing alkaline earth metal (M3) and metal (M4) according to the target composition to prepare a molded body, it is prepared by pressureless sintering under atmospheric pressure.

[0066] Even if pressureless sintering is performed under atmospheric pressure, the relative density of the oxide sintered body of the present invention constituted as described above is 80% or more, and specifically, can be 90% or more. In this case, the upper limit value is not particularly limited. In addition, the specific resistance of the oxide sintered body is 1×10 -2 The lower limit is not particularly limited.

[0067] Moreover, compared with the existing sintered body that does not contain metal (M4), the oxide sintered body composed of the above composition not only has a finer average grain size (D50) of the grains, but also the difference in surface roughness of the sintered body target before and after sputtering is small, thereby having uniform surface properties and excellent thin film properties.

[0068] In one example, the average grain size (D50) of the grains in the oxide sintered body may be 80% or less, specifically 60% or less, and more specifically 40% to 50% of the average grain size (D50) of the grains in the oxide sintered body without the metal (M4). For example, the size (D50) of the grains of the oxide sintered body containing the metal (M4) may be 5 μm to 30 μm, specifically 10 μm to 20 μm. In contrast, the grain size of the oxide sintered body not containing the metal (M4) may be 20 μm to 50 μm.

[0069] Meanwhile, the oxide sintered body of the present invention having the aforementioned composition contains a conductive metal (M4) component, and the oxide thin film formed thereby can have low resistance characteristics.

[0070] In one example, the sheet resistance of the oxide sintered body is less than 60% of the sheet resistance of the oxide sintered body not containing the metal (M4), specifically, it can be less than 50%, and more specifically, it can be 1% to 10%. For example, the sheet resistance of the oxide sintered body containing the metal (M4) or the thin film formed thereof can be 2.60×10 4 Ω / sq to 0.01×10 4 Ω / sq, specifically, it can be 1.30×10 4 Ω / sq to 0.03×10 4 Ω / sq. In contrast, the sheet resistance of an oxide sintered body or thin film not containing metal (M4) can be 3.00×10 4 Ω / sq to 1.60×10 4 Ω / sq.

[0071] The oxide sintered body of the present invention includes more than one crystal phase, and in particular, at least one crystal phase component must include at least one metal (M4) among molybdenum, titanium, chromium, tungsten and copper, which is different from the existing sintered bodies formed by using only metal oxides as reactants. For example, the above-mentioned oxide sintered body may include at least a part of the crystal phase formed by the following reaction formula.

[0072] 2(1-x)MoO2+xNb2O5→2Mo (1-x) Nb x O2+2.5xO2

[0073] MgO+Nb2O5→MgNb2O6

[0074] CaCO3→CaO+CO2

[0075] CaO+Nb2O5→CaNb2O6

[0076] 2MgO+MoO2→Mg2Mo3O8

[0077] In one example, the oxide sintered body may include a MoO2 phase in which Nb2O5 is partially dissolved, for example, Mo 1- x Nb xO2 (wherein x is 0 to 0.25, specifically, 0.15 to 0.25) as the main crystal phase, MgNb2O6, CaNb2O6, Mg2Mo3O8 and / or molybdenum as the sub-crystal phase may be contained. More specifically, at least a portion of the aforementioned main crystal phase and the sub-crystal phase contain a form in which molybdenum is dispersed. The area ratio (specific area) of the above-mentioned crystal phase is not particularly limited. For example, relative to the total crystal phase of the above-mentioned sintered body, more than 25% of the main crystal phase may be contained, and more specifically, the main crystal phase in the range of 27% to 83% may be contained.

[0078] On the other hand, the oxide sintered body of the present invention may contain stoichiometric molybdenum oxides such as MoO2 and MoO3 based on the final product, but may not substantially contain stoichiometric molybdenum oxides such as Mo4O 11 、Mo 17 O 47 、Mo5O 14 、Mo8O 23 、Mo9O 26 and Mo 18 O 52 Among them, "substantially free of" may mean that the inevitable content is 2.0 weight percent or less, specifically, 1.0 weight percent or less, and more specifically, 0.5 weight percent or less relative to 100 weight percent of the above-mentioned oxide sintered body.

[0079] Preparation method of oxide sintered body and sputtering target

[0080] Hereinafter, a method for producing an oxide sintered body and a sputtering target according to an embodiment of the present invention will be described. However, the method is not limited to the following method, and the steps of each process may be modified as needed or the above-mentioned steps may be selectively mixed.

[0081] The present invention is to prepare a sputtering target, that is, to prepare a mass by heat treating a raw material powder of a metal or ceramic. For example, when preparing the above-mentioned oxide sintered body and sputtering target, the raw material powder of the metal or ceramic is MoO2 and / or MoO3, Nb2O5 as a base material, and additional elements are added and mixed to finally form a sputtering target.

[0082] According to one embodiment of the above-mentioned preparation method, the method comprises: step (i), preparing raw material powder by mixing molybdenum oxide (M1), niobium oxide (M2), metal oxide (M3) containing at least one alkaline earth metal, and metal (M4) according to the target composition ("step S10"); step (ii), preparing a molded body using the mixed raw material powder ("step S20"); and step (iii), preparing a sintered body by heat treating the molded body at atmospheric pressure in an inert gas atmosphere at a temperature of 1200 to 1600°C ("step S30").

[0083] Hereinafter, the above-mentioned production method will be described according to each process step.

[0084] (i) Preparing raw material powder ("step S10")

[0085] The above step S10 is a step of preparing raw material powders including molybdenum oxide (M1), niobium oxide (M2), metal oxide (M3) containing at least one alkaline earth metal, and metal (M4). Specifically, after weighing the molybdenum oxide (M1), niobium oxide (M2), one or more alkaline earth metal oxides (M3) selected from CaCO3 and MgO, and metal (M4) selected from molybdenum, titanium, chromium, tungsten and copper powders according to the target composition, the powders are put into a mixer, crushed and mixed to prepare a mixture.

[0086] When the raw material powders are mixed, conventional additives known in the art may be further included as required, such as binders, dispersants, defoamers, etc. In this case, the amount of the additives used may be appropriately adjusted within the conventional range known in the art, for example, 0.01 weight percent to 10 weight percent may be used relative to the total weight of the powders in the slurry (e.g., 100 weight percent).

[0087] The mixing and pulverizing of the raw material powders are not particularly limited and can be performed using conventional ball mills, grinders, bead mills, etc. known in the art. For example, the raw materials can be mixed and pulverized using a wet bead mill using zirconia balls, and then the powders can be spheronized (spray dried) and then sieved to obtain the final powder.

[0088] After adding pure water, defoamer, plasticizer, binder, etc. equivalent to about 2 times the weight of the raw material powder, a mixing operation is performed for about 2 hours using a stirrer to fully mix.

[0089] Then, 0.8Φ zirconia beads (about 2 kg) are placed in a 1L container (Vessel) made of zirconia material and the raw materials mixed with pure water are placed to be fully crushed. In this case, the speed of the bead mill is not particularly limited, for example, it can be about 2000rpm to 4000rpm, specifically, it can be 2500rpm to 3500rpm, more specifically, it can be about 3000±200rpm, and 4 liters to 6 liters of raw materials are placed per minute, specifically, 4.5 liters to 6.5 liters are placed, and more specifically, the raw materials are placed at a speed of 5 liters per minute.

[0090] After being fully pulverized, a microspherical powder is prepared by using a spray drying device. Then, the sample powder and the waste powder are separated using a 90-110 mesh, specifically, a 100 mesh, mesh as required.

[0091] (ii) Preparing a Molded Body (“Step S20”)

[0092] The above step S20 is a step of preparing a molded body using the prepared raw material powder. More specifically, the raw material powder is put into a molding machine and subjected to a molding process to prepare a molded body of a specified specification.

[0093] In order to improve the density of the molded body, more than one molding process, specifically, a secondary molding process can be performed. For example, the primary molding process is to prepare a primary molded body by putting raw material powder into a uniaxial molding machine, and the secondary molding process can use a static pressure molding machine (CIP).

[0094] The conditions of the above-mentioned primary molding process are not particularly limited and can be appropriately adjusted within the usual conditions known in the technical field to which the present invention belongs. For example, a primary molded body is prepared using a superhard material mold of 50Φ specification according to a fixed powder weight. In this case, the primary molding can be carried out with the minimum pressure required to form the shape, specifically, it can be carried out at a pressure of about 10Mpa and maintained at a level of about 1 minute. Then, the second molding is carried out by hydrostatic molding (CIP) at 200MPa for several hours. In this case, since the secondary hydrostatic molding is carried out together with an organic solvent including water, it can be carried out in a state of being placed in an acrylic sealing material (e.g., a bag).

[0095] (iii) Preparing a sintered body (“Step S30”)

[0096] In the above step S30 , a sintered body is prepared by sintering the prepared compact under prescribed conditions.

[0097] In this case, the sintering conditions are not particularly limited and can be appropriately adjusted within the usual conditions known in the technical field to which the present invention belongs. For example, pressureless sintering can be performed at a temperature of 1200° C. to 1600° C. for 1 to 20 hours, and specifically, pressureless sintering can be performed at a temperature of 1350° C. to 1550° C. for 3 to 7 hours. The above sintering can be performed in an oxygen atmosphere, or, for the purpose of improving the electrical conductivity brought about by partial oxygen deficiency, can be performed under inert gas conditions such as nitrogen or argon.

[0098] As a specific example of the above step S30, the prepared molded body is placed in an alumina crucible of a specified specification for sintering. In this experiment, in order to confirm the difference in characteristics between the molded body before heat treatment and the pressureless sintered body after heat treatment, various physical properties are compared by measuring the weight, diameter, height, etc. of the corresponding molded body and sintered body (see Table 2 and Table 3 below). Figures 4 to 5 ).

[0099] The relative density of the pressureless sintered body prepared by this process may be 80% or more, specifically, 85% or more, and more specifically, 90% or more. In this case, the upper limit value is not particularly limited.

[0100] (iv) Preparation of sputtering target

[0101] Next, the sintered body is taken out and processed. For example, after the sintered body is taken out after the heat treatment, the upper and lower parts of the target can be processed to 1 mm or more in order to grind the surface of the target.

[0102] Then, a finished sputtering target is prepared by diffusion bonding and final processing known in the art to which the present invention belongs.

[0103] Specifically, the sintered body obtained in the above step S30 is bonded to a backing plate. In this case, indium can be used as a binder, preferably, so that the bonding rate is 95% or more. Then, the final sputtering target is obtained by processing the backing plate surface with a processing device to a final target thickness, and performing bead blasting and / or arc spraying on the backing plate surface.

[0104] The metal oxide target can be prepared by the above process. The target density of the prepared target is 90% or more, and specifically, preferably 95% or more.

[0105] Oxide film

[0106] Another example of the present invention is a metal oxide thin film deposited by using the above molybdenum oxide-based target. Such a metal oxide thin film can be formed by sputtering using the above sintered body as a target.

[0107] The above oxide thin film may have a slight difference in composition depending on the evaporation atmosphere, but since it is prepared by sputtering the above oxide target, the composition is substantially the same as that of the above target. Therefore, it is possible to form a film with a relative density characteristic of more than 80% and a 1×10 -2 Excellent resistance below Ωcm compared to characteristic oxide thin film.

[0108] Furthermore, the oxide film of the present invention controls the grain growth of the sintered body by adding a high content of metal (M4) dopants such as molybdenum, so that the low resistance and low reflection characteristics of the oxide film can be ensured as the conductivity increases. Furthermore, by adding a specified range of metal oxides and metals to the molybdenum oxide as the main raw material, the chemical resistance and heat resistance and other characteristics can be improved by optimizing the proportion and composition of the molybdenum oxide. Furthermore, by adding a small amount of specific dopants (M3, M4) to improve the sintering characteristics and increase the density, the difficult-to-sinter Mo-Nb-O type sputtering target can have a high density and excellent resistivity by using pressureless sintering instead of the existing pressure sintering.

[0109] In one example, the reflectivity of the oxide film to light with a wavelength of 550 nm is less than 25%, and more specifically, it can be 5% to 18%. The reflectivity can be measured by a method known in the technical field to which the present invention belongs. For example, the reflectivity to the average wavelength of 360 to 740 nm and / or the slope length of 550 nm can be measured on the surface of the substrate on which the metal oxide film is formed. In this case, the lower limit of the light reflectivity is not particularly limited.

[0110] In another example, in the relevant film thickness to The sheet resistance of the oxide film is 2.60×10 4 Ω / sq or less, more specifically, 1.30×10 4 Ω / sq to 0.03×10 4 Ω / sq.

[0111] The metal oxide thin film of the present invention can be formed (evaporated) by a conventional sputtering method known in the technical field to which the present invention belongs. As an embodiment of the above-mentioned preparation method, it includes the step of installing the above-mentioned molybdenum oxide pressureless sintered body sputtering target and then performing room temperature evaporation in an oxygen and / or argon atmosphere in a vacuum tank. In this case, a DC sputtering machine (Sputter) can be used for sputtering.

[0112] The substrate and sputtering device used can be conventional substrates and sputtering devices known in the technical field to which the present invention belongs without limitation. For example, oxygen, oxygen and high-purity argon or argon (Ar) gas are provided at a rate of 80 to 110 sccm (standard cubic centimeters per minute) in a vacuum tank, specifically, at a rate of 95 to 105 sccm, and evaporation can be performed at room temperature (RT) without heating the substrate on which the film is formed. In addition, the power density of the DC sputtering machine can be 0.5 to 3.6 W / cm 2 , more specifically, it can be 1.0 to 2.0 W / cm 2 The thickness of the molybdenum metal oxide film can be to However, it is not limited to this. In addition, the physical property evaluation of the film can be carried out in the following After evaporation of molybdenum oxide film The copper film was then evaluated by measuring the reflectivity and sheet resistance of the film on the glass surface.

[0113] The oxide film obtained as described above can be used in various ways when preparing semiconductor devices, for example, it can be used to form circuits or to form electrodes when preparing semiconductors. In particular, the above-mentioned metal oxide film can expand the scope of application in the thin film transistor structure of liquid crystal displays and organic light-emitting diodes by ensuring low resistance and low reflection characteristics. For example, while ensuring low reflection characteristics, it can be used as a gate layer material of a thin film transistor, and while ensuring low resistance and low reflection characteristics at the same time, it can be used as one or more of the gate layer, source layer and drain layer of a thin film transistor. In this way, when the film of the present invention is used as a gate layer, source layer, drain layer material contained in a thin film transistor and / or in a barrier layer of these layers, the contact resistance can be reduced, and it has excellent transparency and low refractive index, so the physical properties of the thin film transistor can be improved.

[0114] The molybdenum oxide sputtering target of the present invention and the oxide thin film formed therefrom can be effectively used in various technical fields. For example, it can be applied to the following devices without limitation: various display devices such as liquid crystal display devices or organic electroluminescent display devices, for example, information transmission devices such as liquid crystal display, plasma display (PDP), organic light emitting diode, light emitting diode (LED) and other flat panel displays; touch panels of surface light source lighting devices such as organic light emitting diode, light emitting diode; mobile phones, tablet computers and / or information transmission devices using the same.

[0115] Hereinafter, the present invention will be described in detail by way of examples, but the following examples are only for illustrating the present invention, and the present invention is not limited to the following examples.

[0116] Example 1-5: Preparation of a sintered body with added MoO2-Nb2O5, a and added molybdenum

[0117] Molybdenum oxide (M1), niobium oxide (M2), alkaline earth metal oxide (M3) and metal (M4) were mixed in the composition ratio shown in Table 1 below to prepare a molded body.

[0118] When preparing the molded body, most samples were prepared as 127 Φ discs, and in the case of a part of the composition, the size was prepared as 50 Φ. Then, the oxide sintered bodies of Examples 1 to 5 were prepared by heat treatment at a temperature of about 1350 to 1550° C. for 6 hours in a nitrogen atmosphere using a heat treatment device.

[0119] Table 1

[0120]

[0121] Comparative Example 1-2: Preparation of a sintered body with addition of MoO2-Nb2O5 and α

[0122] Except for changing the composition to that shown in Table 1 above, a 127Φ disk was prepared in the same manner as in the above embodiment. In the case of a part of the composition, a disk of 50Φ was prepared. Then, the oxide sintered bodies of Comparative Examples 1 and 2 were prepared by heat treatment at a temperature of about 1350 to 1550°C for 6 hours in a nitrogen atmosphere using a heat treatment device.

[0123] Experimental Example 1: Evaluation of the physical properties of the molded product

[0124] The physical properties of each of the molded bodies prepared in Examples 1 to 5 and Comparative Examples 1 and 2 were evaluated in the following manner.

[0125] Specifically, the diameter (D) and height (T) of each molded body were measured with a vernier caliper, and the weight (Mass) was weighed with a scale. Furthermore, the relative density was calculated by converting the added amount of each weight into volume percentage and converting the level compared with the theoretical density into percentage, and the results are shown in Table 2. In this case, the density of the measured sample was calculated as weight / volume, and when a plurality of the same samples were prepared, it was expressed as an average value.

[0126] For reference, each sample in Table 2 below had a low relative density because it was not sintered, and the relative density of each sintered body after sintering (heat treatment) showed a level of 96%.

[0127] Table 2

[0128]

[0129] Experimental Example 2: Evaluation of the average grain size of the sintered body

[0130] The sintered bodies heat treated at 1450° C. were used to evaluate their structural changes and average grain sizes.

[0131] Specifically, the sintered bodies of Examples 1 to 5 prepared without pressure and Comparative Examples 1 to 2 prepared under the same conditions were used as samples. The two samples were cut into 10×10×10 mm specifications using a metal blade, and then polished for several minutes using SiC sandpaper (paper) #100 to #2000 using a polisher, and finally prepared using 1 μm paste and ultra-fine fiber cloth. Then, the sample was immersed in hydrogen peroxide at a temperature of about 200°C for 1 minute and heat-treated so that the surface of the structure could be exposed.

[0132] In addition, for the measurement of the average particle size of the sintered body, each sample was observed at the same magnification of 300 using FE-SEM (Hitachi, S-4800), and 5 lines were randomly drawn on the measured image and calculated for about 100 particles using the linear intercept method according to the following mathematical formula 1. The results are as follows: Figures 1 to 3 shown.

[0133] Mathematical formula 1

[0134] D=1.56×C / MN

[0135] In the above formula, D = average particle diameter, C = total length of the line, M = magnification, and N = number of particles on the line.

[0136] The experimental results show that in the case of Comparative Example 1 composed of molybdenum oxide and niobium oxide, the average grain size of the sintered body is about 11.4 μm. However, the relative density of Comparative Example 1 is less than 70%, which is not suitable for use as a sputtering target. In addition, in the case of Comparative Example 2 containing molybdenum oxide and niobium oxide as basic components and containing alkaline earth metal oxide, the average grain size is 30.2 μm, and it can be seen that the average grain size of the sintered body is slightly increased due to the alkaline earth metal dopant.

[0137] In contrast, in the case of Examples 1 to 5, which contain molybdenum oxide and niobium oxide as basic compositions and contain alkaline earth metal oxide and molybdenum metal, it can be confirmed that the average particle size is finer than that of Comparative Example 2 (refer to Figures 1 to 3 ).

[0138] Experimental Example 3: Evaluation of sintered body density and shrinkage

[0139] After each sample prepared in Examples 1 to 5 and Comparative Examples 1 and 2 was subjected to heat treatment, changes in the physical properties of each sintered body were measured.

[0140] (1) Evaluation of density after heat treatment

[0141] The physical properties of the sintered body after heat treatment were evaluated by measuring in the same manner as in Experimental Example 1. For example, the relative density calculated by measuring the diameter, height and weight of the sintered body after heat treatment is shown in FIG. Figure 4 shown.

[0142] The experimental results show that in Examples 1 to 5, as the sintering temperature increases from 1350°C to 1550°C, the relative density also increases significantly (refer to Figure 4 ). In comparison, in the case of Comparative Example 1, it can be seen that the relative density of the molded body is lower or similar as the sintering temperature increases, while Comparative Example 2 has a density similar to that of the embodiment.

[0143] (2) Evaluation of shrinkage before and after heat treatment

[0144] The shrinkage rate is calculated by measuring the diameter and height of the molded body before heat treatment and the sintered body after heat treatment. Figure 5 shown.

[0145] The experimental results show that the shrinkage rate of Comparative Examples 1 to 2 does not change much with the heat treatment. In contrast, it can be seen that the shrinkage rate of the sintered bodies of Examples 1 to 5 changes relatively greatly with the heat treatment (refer to Figure 6 ). For example, in the case of the embodiment, the shrinkage rate in the sintering at 1400°C increases sharply compared with the sintering at 1350°C, which can be regarded as the normal sintering reaction at a temperature above 1400°C due to the addition of molybdenum metal. Such high shrinkage rates before and after heat treatment indicate that most of the pores existing in the molded body are removed by heat treatment, and it can be seen that the density and density characteristics of the sintered body are significantly improved by heat treatment.

[0146] Experimental Example 4: Evaluation of the specific resistance of the sintered body

[0147] For each of the sintered body samples prepared in Examples 1 to 5 and Comparative Examples 1 and 2, the specific resistance characteristics were evaluated.

[0148] Specifically, all samples used in the evaluation were used as sintered body samples, and the resistance ratio of the samples was measured using Loresta-GX MCP-T700 (Mitsubishi Chemical).

[0149] Table 3

[0150]

[0151] As shown in Table 3, it was confirmed that the oxide sintered bodies of Examples 1 to 5 containing a predetermined metal dopant have more excellent resistivity characteristics than the sintered bodies of Comparative Examples 1 and 2.

[0152] Experimental Example 5: Evaluation of the physical properties of thin films

[0153] After thin films were formed using the sintered bodies prepared in Examples 1 to 5 and Comparative Example 2 as targets, the properties of the thin films were evaluated as follows.

[0154] Specifically, each sintered body is used to prepare a thin film as a low reflection layer under the gate electrode layer. Such a thin film is used to improve the low reflection on the substrate (glass) and the adhesion of the gate electrode.

[0155] (1) Evaluation of sheet resistance characteristics

[0156] Use DC sputtering machine at 0.5~3.6w / cm 2 The target materials including the sintered bodies of Comparative Example 2 and Examples 1 to 5 were deposited on a transparent glass plate in an argon atmosphere at a power density of to The sheet resistance characteristics of each sample were measured using the CMT-SR5000 product (AIT CO. LTD) for the evaporated unit film. The results are shown in Table 4 and Figure 6 shown.

[0157] Table 4

[0158]

[0159] As shown in Table 4, it can be seen that Examples 3 to 5 have lower resistance characteristics than Comparative Example 2.

[0160] (2) Evaluation of reflectivity

[0161] In addition, an electrode was formed on the thin film. A DC sputtering machine was used at 0.5 to 3.6 W / cm 2 The copper target was formed into an electrode in an argon atmosphere with a power density of

[0162] In this state, the reflectivity of the thin film is measured on the surface of the glass substrate. In this case, the reflectivity uses the reflectivity value at an average wavelength of 360 to 740 nm and / or 550 nm. The result is as follows: Figure 7-8 shown.

[0163] The experimental results show that Examples 3 to 5 ensure low reflection characteristics that are superior to Comparative Example 2.

[0164] Experimental Example 6: X-ray diffraction evaluation of sintered body

[0165] In order to confirm the crystallinity of the oxide sintered bodies of Example 1, Example 4, Comparative Example 1 and Comparative Example 2, X-ray diffraction analysis was performed. The results are as follows: Fig. 9 shown.

[0166] It can be confirmed that unlike Comparative Examples 1 and 2 which do not contain metallic molybdenum, the oxide sintered body of Example 4 additionally generates a metallic molybdenum phase, and it is judged that the movement between particles in the sintered body is reduced, thereby reducing the average grain size of the crystal grains (refer to Fig. 9 ).

Claims

1. An oxide sintered body, characterized in that: Include: Molybdenum oxide M1; Niobium oxide M2; at least one alkaline earth metal oxide M3; and One or more metals M4 selected from the group consisting of molybdenum, titanium, chromium, tungsten and copper, The sintered body contains the metal in an amount of 3 to 60 weight percent relative to the total weight of the sintered body.

2. The oxide sintered body according to claim 1, characterized in that The metal M4 is contained in an amount of 5 weight percent to 55 weight percent relative to the total weight of the sintered body.

3. The oxide sintered body according to claim 1, characterized in that The average grain size D50 of the crystal grains in the oxide sintered body is 80% or less compared to the average grain size D50 of the crystal grains in the oxide sintered body not containing the metal M4.

4. The oxide sintered body according to claim 1, characterized in that The sheet resistance of the oxide sintered body is 60% or less compared to the sheet resistance of an oxide sintered body not containing the metal M4.

5. The oxide sintered body according to claim 1, characterized in that The oxide sintered body contains Mo (1-x) Nb x O2 crystal phase and metal M4 crystal phase, wherein x is 0 to 0.

25.

6. The oxide sintered body according to claim 1, characterized in that The oxide sintered body is obtained by mixing molybdenum oxide M1, niobium oxide M2, at least one alkaline earth metal oxide M3 and metal M4 to prepare a molded body, and then pressurelessly sintering the mixture under atmospheric pressure.

7. The oxide sintered body according to claim 1, characterized in that The molybdenum oxide M1 includes at least one of MoO2 and MoO3. The molybdenum oxide M1 is contained in an amount of 20 weight percent to 70 weight percent relative to the total weight of the oxide sintered body.

8. The oxide sintered body according to claim 1, characterized in that The molybdenum oxide M1 and the niobium oxide M2 ​​are contained in an amount of 45.0 weight percent or more and less than 95 weight percent based on 100 weight percent of the oxide sintered body. The content ratio of the molybdenum oxide M1 to the niobium oxide M2 ​​is 80:20 to 45:55 by weight.

9. The oxide sintered body according to claim 1, characterized in that The alkaline earth metal oxide M3 includes one or more selected from the group consisting of CaCO3 and MgO.

10. The oxide sintered body according to claim 1, characterized in that The above-mentioned alkaline earth metal oxide M3 is contained in an amount greater than 0 weight percent and less than or equal to 10 weight percent based on 100 weight percent of the above-mentioned oxide sintered body.

11. The oxide sintered body according to claim 1, characterized in that The weight ratio of the at least one alkaline earth metal oxide M3 to the metal M4 is 1:1-20.

12. The oxide sintered body according to claim 6, characterized in that The average grain size of the crystal grains constituting the pressureless sintered oxide sintered body is 5 μm to 30 μm. The specific resistance is 3×10 -3 Ωcm or less, The relative density is above 80%.

13. A sputtering target, characterized in that: A sintered oxide body comprising the oxide sintered body according to any one of claims 1 to 12.

14. An oxide thin film, characterized in that: The sputtering target is formed from the sputtering target according to claim 13.

15. The oxide thin film according to claim 14, characterized in that: The reflectivity of light with a wavelength of 550nm is less than 25%. Thickness to When the sheet resistance is 2.6×10 4 Ω / sq or less.

16. A method for preparing an oxide sintered body according to claim 1, characterized in that: include: Step (i), preparing a raw material powder by mixing molybdenum oxide M1, niobium oxide M2, a metal oxide M3 containing at least one alkaline earth metal, and a metal M4 according to a target composition; Step (ii), preparing a molded body using the mixed raw material powders; as well as Step (iii) heat-treating the molded body at a temperature of 1200 to 1600° C. in an inert gas atmosphere at atmospheric pressure to prepare a sintered body.

Citation Information

Patent Citations

  • Sputtering target, low resistivity, transparent conductive film, method for producing such film and composition for use therein

    CN101277910A

  • Black mixed oxide material and method for manufacturing same

    CN110730766A

  • Molybdenum oxide-based sintered body, thin film using sintered body, thin film transistor including thin film, and display device

    CN115819083A

Cited By

  • Low-reflection tungsten-based ceramic target material as well as preparation method and application thereof

    CN120796758A

  • Molybdenum oxide target material and preparation method and application thereof

    CN121554293A